2018
DOI: 10.1007/s00464-018-6574-5
|View full text |Cite
|
Sign up to set email alerts
|

Operating hurts: a study of EAES surgeons

Abstract: Background Work-related pain and discomfort experienced by surgeons is widely reported in the literature. A survey was, therefore, conducted to explore this issue among members of the European Association for Endoscopic Surgery (EAES). Methods The survey was emailed to 2980 EAES members in 2017 enquiring about their working practice, musculoskeletal (MSK) pain and burnout. Results A total of 569 (19%) surgeons responded, of whom 556 were prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 37 publications
1
32
0
3
Order By: Relevance
“…[1][2][3][4][5][6][7][8] WMSDs can lead to impaired surgical well-being, leading to higher surgeon disability, decreased quality of life, and reduced career longevity. [8][9][10][11] WMSDs can also lead to reduced patient safety, reduced quality of surgical care, and overall reduced functioning of the surgical healthcare system, which incurs great patient and societal costs. [12][13][14][15] Research efforts to improve surgical ergonomics have been underway during the past 2 decades.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] WMSDs can lead to impaired surgical well-being, leading to higher surgeon disability, decreased quality of life, and reduced career longevity. [8][9][10][11] WMSDs can also lead to reduced patient safety, reduced quality of surgical care, and overall reduced functioning of the surgical healthcare system, which incurs great patient and societal costs. [12][13][14][15] Research efforts to improve surgical ergonomics have been underway during the past 2 decades.…”
mentioning
confidence: 99%
“…Only the 2003 study of the general nursing workforce 15 and the QI project were completed in the United States 16 . Three studies were conducted in Iran; 17,19 two in the Netherlands; 20,21 and the others in Egypt, 22 Europe, 23 Germany, 24 Israel, 25 Sweden, 26 and Turkey 27 …”
Section: Review Of the Literaturementioning
confidence: 99%
“…Researchers used a variety of data collection methods, including survey, 15,16,20,23,24,25 survey with a physical examination, 26 survey with an observation, 17-19 survey with an observation and a skills checklist, 22 survey with observations and interviews, 21 and observations 27 …”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…13 Several studies have also found approximately 50% of surgeons fear they will have a shortened career due to musculoskeletal disorders, with a significant correlation between this fear of a shortened career and burnout. 14,15 Jackson and colleagues employed NASA-TLX and SURG-TLX questions to ask breast surgeons to compare nipple-sparing mastectomy and skin-sparing mastectomy, finding that surgeons reported greater physical symptoms, mental strain, and fatigue with nipple-sparing mastectomy than skin-sparing mastectomy. 16 Together, these findings raise concern that discomfort along with increased cognitive and technical demand over the course of a breast surgeon's career may lead to musculoskeletal disorders and burnout and ultimately shorten surgical careers.…”
Section: Surg-tlx Surgery-task Load Indexmentioning
confidence: 99%